Digital technique to analyze the wear of the slot after orthodontic treatment through fixed multibracket appliances - Mabel Daiana Pimentel-García; Álvaro Zubizarreta-Macho; Jorge Alonso Pérez-Barquero; Clara Guinot Barona; Alberto Albaladejo Martínez (BMC, 2023)
Abstract Introduction To assess the accuracy, repeatability and reproducibility of a measurement digital technique to quantify the wear of the bracket slot walls of the fixed multibracket appliance after orthodontic treatment with the previous measurement traditional technique (scanning electronic microscope (SEM)). Methods A total of 100 fixed multibracket appliances were cemented during the 15 months orthodontic treatment and subsequently removed. The fixed multibracket appliances were submitted preoperatively and postoperatively to a micro-computed tomography (micro-CT) scan to obtain accurate standard tessellation language (STL) digital files of the fixed multibracket appliances and to a preoperatively and postoperatively SEM analysis. Afterwards, pre-operatively and postoperatively STL digital files of each fixed multibracket appliances were aligned using morphometric software with the best fit algorithm. Subsequently, area and volume wear of fixed multibracket appliances was identified, isolated and measured. Results The repeatability and reproducibility of the digital measurement method for the area (mm2) and volume (mm3) were analyzed by Gage R&R statistical analysis. The area wear of the bracket slot walls of the fixed multibracket appliance after orthodontic treatment showed a repeatability of 3.7% and a reproducibility of 0%. The volume of the bracket slot walls of the fixed multibracket appliance after orthodontic treatment showed a repeatability of 0.9% and a reproducibility of 5.6%. However, the traditional measurement technique showed a repeatability of 0.58% and a reproducibility of 33.01%; hence, it was repeatable but not reproducible. Conclusions The digital measurement technique is a reproducible, repeatable, and accurate method for quantifying the wear of the bracket slot walls of the fixed multibracket appliance after orthodontic treatment.